Connected hidden neurons (CHNNet): an artificial neural network for rapid convergence - Shahir, Rafiad Sadat; Humayun, Zayed; Tamim, Mashrufa Akter; Saha, Shouri (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2023.